Dealing with Central Vascular Access Devices: A Qualitative Study on Cancer Patients' Experiences - Martina Torreggiani; Deborah Maselli; Stefano Botti; Genny Mazza; Monia Ferrarini; Monica Guberti (Infermieristica Journal, 2025)
Introduction. Central vascular access devices are widely used in oncology settings due to the significant side effects of chemotherapy on blood vessels. Despite the methodological robustness of the literature, the enhanced integration of patients’ perspectives would enrich the evidence on this topic. This study explores oncology patients' experiences with cVADs (PICC and TIVAD), from insertion to daily life management.